First data on aquaculture of the Tripletail, Lobotes surinamensis, a promising candidate species for U.S. marine aquaculture - Eric Saillant; Nicholas Adams; Jason T. Lemus; James S. Franks; Yonathan Zohar; John Stubblefield; Christopher Manley (Wiley, 2025)
The Tripletail, Lobotes surinamensis, is a warm-water pelagic fish that is increasingly targeted by U.S. anglers. The superior quality of Tripletail flesh coupled with the lack of domestic commercial fisheries stimulated interests to develop aquaculture of this species. In this work, photothermal conditioning of captive-held broodstocks promoted maturation in females, but spontaneous spawning was not observed. GnRHa slow-release implants induced ovulation in late vitellogenic females but fertility remained below 10% when GnRHa was administered alone. However, spawns with high fertility (up to 85%) were obtained when a dopamine antagonist was administered in conjunction with GnRHa implants indicating dopamine inhibition impaired final gamete maturation, in particular sperm production in males, in aquaculture conditions. Tripletail larvae successfully initiated exogenous feeding on enriched rotifers followed by Artemia nauplii and were weaned to prepared feeds at 25 days post hatch, yet with low survival through the late phases of larval culture. Pilot grow-out trials at low density in recirculating systems revealed impressive growth rates averaging over 170 g/month through a market size above 1 kg. While protocols for hatchery culture and growout still need to be optimized, current data suggest that Tripletail could become a successful species for U.S. marine aquaculture.